The association of sperm BAX and BCL-2 gene expression with reproductive outcome in Oligoasthenoteratozoospermia cases undergoing intracytoplasmic sperm injection: A case-control study - Fatemeh Babaei; Maryam Khoshsokhan Muzaffar; Rahil Jannatifar (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: The B-cell lymphoma 2 (BCL-2) protein is one of the members of the BCL-2 associated X (BAX) protein family that acts as an inducer of apoptosis. Objective: The present study aims to investigate the association between BAX and BCL-2 gene expression with reproductive outcome, in cases undergoing intracytoplasmic sperm injection. Materials and Methods: In this case-control study, 50 men were divided into healthy fertile and oligoasthenoteratozoospermic infertile men (n = 25/each). They were subjected to history taking, clinical examination, and semen analysis. Expression of BAX and BCL-2 genes were measured using real-time polymerase chain reaction. The DNA fragmentation index was measured using the sperm chromatin dispersion assay technique. Using World Health Organization criteria, sperm parameters were evaluated. Results: Evaluation of apoptosis-related genes showed that oligoasthenoteratozoospermic significantly increased mRNA expression of BAX, and significantly decreased mRNA expression of BCL-2, when compared with control. Moreover, the BAX/BCL-2 ratio was significantly higher in oligoasthenoteratozoospermic compared to the normozoospermic group (p = 0.01). Also, this study showed that the BAX and BCL-2 genes expression had a significant correlation with sperm quality, and DNA fragmentation in the oligoasthenoteratozoospermic group (p = 0.01). The oligoasthenoteratozoospermic men, had a considerably lower proportion of fertilization rate and good-quality embryos at the cleavage stage than the normozoospermic subjects (p = 0.01). A significant correlation was observed between the expression of BAX and BCL-2 genes, fertilization, and embryo quality (p = 0.01). Conclusion: We concluded that the sperm BAX/BCL-2 ratio demonstrates a significant correlation with fertilization rate and embryo quality.